Pendekatan Siyāsah Syar‘Iyyah Dalam Menangani Isu Perundangan Jenayah Semasa Di Malaysia: Siyāsah Syar‘iyyah Approach in Dealing with Current Criminal Legislation Issues in Malaysia - Abdul Khalil, Shahidra (Jurnal Fiqh, 2022)
International legal developments may have an impact on the formulation of laws and policies in a country. In terms of crime, for example, there are international calls for some municipal laws to be revised. Among them is a call to repeal the law prohibiting attempted suicide and the death penalty. This abolition step is said to be required to ensure modern society's welfare. However, the government must carefully study this issue while keeping the context of the country in mind. Furthermore, some international laws may be incompatible with Shariah. In dealing with this issue, the government may apply the siyasah syar'iyyah approach in making decisions and considering appropriate actions. The aim of this paper is to discuss the concept and elements of siyasah syar'iyyah, particularly in the context of criminal law implementation. Then, its application in dealing with issues pertaining to attempted suicide and death penalty legislation in Malaysia is discussed. Thematic and comparative analysis methods were used in the study. The study finds that the government has extensive powers in enforcing policies and laws that are appropriate to current needs, particularly when it comes to the crime of takzir. However, there are certain guidelines to ensure that the actions taken by the government is fair (siyasah 'adilah) and coincide with shariah. In Malaysian context, it was found that the process of reviewing the related laws has taken into account the current reality (fiqh al-waqi'), makes considerations of the public interest (maslahah) and harm (mafasadah) (fiqh al-muwazanat) and deliberate the priorities (fiqh al-awlawiyyat) which are among the elements of siyasah syar'iyyah. Thus, it is hoped that further government’s actions in future will benefit the people.